ASPEK PENGETAHUAN DAN SIKAP IBU TENTANG MANAJEMEN LAKTASI - Hardianti, Hardianti; Resmi, Dewi Candra; Nordianiwati, Nordianiwati; Nur Farida, Lisnawati; Laisouw, Meilany (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Lactation management is all the efforts made to help mothers achieve success in breastfeeding their babies. This effort is carried out by the mother especially in the exclusive breastfeeding period, namely the first 0-6 months after childbirth. Based on a survey of the number of deliveries in the Kampar Kiri Hulu Health Center working area in 2022 as many as 34 deliveries, there are still lactation management problems. This study is an observational analytic quantitative study with a cross sectional design. The sampling technique was purposive sampling. Data collection tools using a research questionnaire. Data analysis was done univariate and bivariate using SPSS program. The results showed that there was a relationship between maternal knowledge (p value 0.017) and maternal attitude (p value 0.014) towards lactation management in mothers in the working area of the Kampar Kiri Hulu Health Center. It is suggested to the Puskesmas of Kampar Kiri Hulu Health Center to continue to improve counseling to pregnant women who check their pregnancy so that when giving birth later they can carry out Lactation Management properly and correctly and for the community, especially post partum mothers, it is hoped that they will continue to improve their knowledge both about Lactation Management and about baby care so that they can care for and nurture their babies properly and optimally.Keywords: Lactation Management, Knowledge, Attitude